A Multicenter Study of the Clinical Features of Allergic Rhinitis in Central China. Issue 5 (September 2014) - Chen, Jianjun; Zhao, Yan; Li, Bin; Zhang, Quanming; Wan, Lijia; Liu, Jun; Tian, Xingde; Li, Guoyi; Zhou, Jie; Zhang, Long; Wang, Pengju; Cheng, Qi; et al.
Background: Several epidemiological surveys of allergic rhinitis (AR) have been conducted in China. However, the clinical features of AR are still not clear enough. The aim of the current study was to perform a multicenter investigation to evaluate the clinical features of AR in China. Methods: A multicenter investigation was performed in 13 allergy centers in central China. A disease-related questionnaire was completed by each patient themselves or with guardian assistance after the diagnosis of AR. The clinical features of AR and allergen profile were analyzed. Results: Eleven thousand four patients who were diagnosed with AR were recruited in this study. The percentages of classification of AR according to the Allergic Rhinitis and Its Impact on Asthma guidelines were 9.7% intermittent mild (IM), 3.1% persistent mild (PM), 33.9% intermittent moderate–severe (IMS), and 53.3% persistent moderate–severe (PMS). There were 61.6 and 42.2% AR patients who had concomitant ocular or lower respiratory symptoms in clinic. The occurrence of ocular and lower respiratory symptoms was found to be gradually increased from IM, PM, and IMS to PMS. Cold air and temperature change were the two most common factors triggering the nasal symptoms. Dermatophagoides pteronyssinus and Dermatophagoides farinae were the most important allergens of central China. Conclusions: This study has contributed to a better understanding of clinical features of AR in China.